Installation of First Medium Energy Medical Cyclotron in Bangladesh at National Institute of Nuclear Medicine and Allied Sciences (NINMAS) for PET radiopharmaceuticals Production - Ul Azim, Mohammad Anwar; Biswasarma, Sanchoy Chandra; Uddin, Jashim; Islam, Md Ariful; Hossain, Nahid; Mia, Md Shohag; Mehdi, Hasan; Kabir, Md Alamgir; Mamun, Mustafa; Begum, Ferdoushi; et al. (Bangladesh Journal of Nuclear Medicine, 2022)
PET-CT (positron emission tomography and computed tomography) is a gold-standard cancer imaging tool for diagnosis and management, as well as prognostic information based on treatment. Positron-emitting radionuclide 18F (Fluorine) is generated by accelerating particles to energies high enough to cause a certain nuclear reaction 18O(p,n)18F within the particle accelerator, the cyclotron. Mannose triflate is converted to 2-[18F] Fluoro-2-deox-D-yglucose ([18F]FDG) via nucleophilic reaction. Under the ownership of Bangladesh Atomic Energy Commission installed a medium energy (18/9 MeV, IBA) Cyclotron at National Institute of Nuclear Medicine and Allied Sciences (NINMAS). The facility was established in the oncology Building (Block F) of Bangabandhu Sheikh Mujib Medical University (BSMMU). Cyclotron vault and the Control room are located in the underground i.e. basement floor. Each wall of the cyclotron vault and ceiling is made of concrete with a density of 2.35 g/cm3 and a thickness sufficient to shield gamma and neutron radiation. On the ground floor, there are Synthesis room, Quality control laboratory, and the Decontamination room. PET-CT rooms are located on the first floor. Identification, Radionuclide purity (Gamma spectrum detection and half-life measurement), Radiochemical Purity, Chemical purity, Residual solvent measurement, pH measurement, Sterility, and bacterial endotoxins (LAL test) are performed to maintain the quality of the product. The current uses of the Cyclotron are mostly for the synthesis of 18F-FDG. Bangladesh J. Nuclear Med. 24(1&2): 48-50, 2021